Pengaruh Model Problem Based Learning Menggunakan Padlet Terhadap Hasil Belajar Peserta Didik Mata Pelajaran Informatika di SMKN 2 Guguak - Khairatunnisa Khairatunnisa; Winda Agustiarmi (Educational Journal, 2026)
The low learning outcomes of students in Informatics subjects in Vocational High Schools (SMK) indicate the need for the implementation of innovative and effective learning models. One alternative that can be used is the Problem Based Learning (PBL) model supported by digital learning media such as Padlet to improve student activity and learning outcomes. This study aims to describe the effect of the Problem Based Learning model using Padlet on student learning outcomes in Informatics subjects at SMKN 2 Guguak. This type of research is Experimental research. The experimental research method is a method used to determine the effect of a treatment on another thing in controlled conditions. This study used a quasi-experimental design. The population of this study was all 214 class X students, and the samples taken were 2 classes, namely X MPLB 1 AND X MPLB 2, totaling 64 people. The results of the study after the implementation of the Problem Based Learning Learning Model using Padlet showed an increase in student learning outcomes in Informatics subjects. In the Experimental class, namely class X MPLB 1, there was an increase in the Mean in the Pretest from 51.41 to 77.25 in the Posttest, an increase in the median from 48 to 80, an increase in the mode from 48 to 75, and a standard deviation from 12.74 to 9.38. In the experimental class, namely X MPLB 1, there was an increase in learning outcomes of 50.26%. While in the control class, namely class X MPLB 3, there was an increase in the Mean in the Pretest from 53.48 to 71.51 in the Posttest, an increase in the median from 52 to 70, an increase in the mode from 60 to 80, and a standard deviation from 14.29 to 10.64. In the control classes, there was an average increase of 33.71%. Thus, it can be concluded that the application of the Problem Based Learning model using Padlet is effective in improving student learning outcomes in Informatics subjects at SMKN 2 Guguak.